Determinan Kinerja Keuangan UMKM Kuliner Di Kota Solo - Ririn Wulandari; Pardi Pardi; Astuning Saharsini; Era Trianita Saputra (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the effect of financial management (X1), application of accounting information systems (X2), quality of human resources (X3), utilization of e-commerce (X4) on financial performance (Y) Culinary UMKM in Solo City. The samples taken were 100 respondents, using the slovin formula. The method used in this data analysis technique uses instrument data testing, classical assumption testing, multiple linear regression and hypothesis testing. The method of collecting data is by distributing questionnaires to the heads of culinary UMKM actors in the city of Solo. The results showed that the variables of financial management (X1), application of accounting information systems (X2), quality of human resources (X3), utilization of e-commerce (X4) had a positive effect on the financial performance (Y) of culinary UMKM in Solo.